Comparative analysis of organic and inorganic amendments on maize yield and soil health in clay loam soil - Sanaullah; Ghulam, Said; Khan, Qudrat Ullah; Arsalan, Muhammad; Ullah, Rehmat; Latif, Abdul; Khan, Madeeha; Ahmad, Ijaz; Latif, Rizwan; Sayed, Sairah; Muhammad, Jan; Bilal, Muhammad; et al. (Journal of Pure and Applied Agriculture, 2024)
Maize (Zea mays L.) is widely regarded as a valuable food and fodder crop. Organic and inorganic nutrients are required for crop growth and soil health improvement. This study was conducted at experimental site of Gomal University Dera Ismail Khan, KP, Pakistan, and aimed to evaluate the performance of maize fertilized with organic and inorganic fertilizers in clay loam soil. The organic amendments were farmyard manure (FYM), poultry manure (PTM), and pressmud (PM), whereas the inorganic fertilizers were N, P2O5, and K2O. As a control, no ameliorants were added to the soil. The experiment was done in a randomized complete block design with three replications. The results show that when NPK @ 150+100+60 kg/ha-1 was given to maize crop, there was a higher increase rate in terms of plant height, number of plants per plant, cob weight, grain weight, thousands grain weight, grain yield, biomass yield in NPK treated soil in comparison to FYM, PTM, PM, and control (2019 and 2020). Similarly, economic study revealed that soil treated with inorganic fertilizer had the highest benefit-cost ratio (BCR) compared to other treatments. Furthermore, the findings indicate that organic additions boosted the NPK concentration of the soil. Conclusively, NPK application appears to be more successful than organic nutrition sources for maize productivity.